Expression Analysis of Canine CMTM6 and CMTM4 as Potential Regulators of the PD-L1 Protein in Canine Cancers - Takeuchi, Hiroto; Konnai, Satoru; Maekawa, Naoya; Minato, Erina; Ichikawa, Yoshiki; Kobayashi, Atsushi; Okagawa, Tomohiro; Murata, Shiro; Ohashi, Kazuhiko (Frontiers in Veterinary Science, 2020)
Cancer is one of the most significant causes of death in dogs. Antibody drugs targeting the PD-1/PD-L1 axis represent a promising immunotherapy for both human and canine cancers. However, the regulation mechanisms of PD-L1 expression in canine cancers require further investigation to better understand the resistance mechanisms to anti-PD-L1 therapy. Recent reports have shown that CMTM6 and CMTM4 are critical regulators of PD-L1 protein expression in human cancer cells. By preventing PD-L1 from lysosome-mediated degradation, CMTM6 maintains PD-L1 expression on the cell surface. However, the literature has not reported on CMTM6 and CMTM4 in dogs, and their functions are completely unknown. To reveal a regulation mechanism of PD-L1 in canine cancers, this study firstly identified the gene sequences of CMTM6 and CMTM4. Then, the expression analysis of these proteins was performed by immunohistochemistry. Furthermore, the functions of CMTM6 and CMTM4 in regulating PD-L1 expression were examined by gene knockdown of CMTM6 and CMTM4. Canine CMTM6 and CMTM4 displayed high amino acid sequence identities compared with those of humans and mice. An immunohistochemical analysis using cross-reactive antibodies revealed that canine malignant melanoma and osteosarcoma express CMTM6, CMTM4, and PD-L1 simultaneously. Gene knockdown of CMTM6 and CMTM4 with RNA interference significantly reduced the cell surface expression of PD-L1 in a canine cell line. These results suggest that CMTM6 and CMTM4 are regulators of PD-L1 expression in canine cancers and could serve as potential therapeutic targets to enhance antitumor immunity.